Modified Ileal Neobladder: Experience of 37 Cases (Bangladesh Journal of Urology, 2020)
Bladder cancer is the second most common malignancy of genitourinary tract. About 20% cases are muscle invasive and most of the non-muscle invasive bladder cancer progressed to muscle invasion with time. The standard care for organ confined muscle invasive bladder cancer is radical cystectomy followed by urinary diversion. Orthotopic bladder substitution is considered standard urinary diversion after radical cystectomy in patients who have no urethral malignancy and intact external urethral sphincter. Neobladder constructed from ileum as described by Studer is considered standard and followed by most centers worldwide since 1985. We modified the procedure to improve the outcome and minimize post-operative complications by reducing the length of ileum used for construction of neobladder in 37 patients. Voiding, storage function and complications were evaluated during follow-up period up to 24 months after surgery. Three patients died during follow-up period of which 2 from metastatic disease and one from unrelated cause. Daytime and night-time continence rates were 86.49% and 78.38% respectively. Average functional capacity (437ml), maximum flow rate(15.7ml/s) and mean post void residual urine (44ml) during the period of evaluation. Clean intermittent self-catheterization needed in 67.57% patients due to incomplete emptying during early postoperative period but after 3 months most of the patients learnt to void without any aid. Upper tract dilatation found in one patient due to stricture at urethrovesical junction and required endoscopic incision and dilatation later. 12 patients had an urodynamic study at 12 months after surgery and found low pressure reservoir with small residual urine in all cases. Modified ileal neobladder is a safe and reliable procedure with satisfactory short-term result.Bangladesh Journal of Urology, Vol. 22, No. 1, January 2019 p.20-24